LEGAL PROTECTION OF TOURISTS AS A FORM OF TOURISM INVESTMENT IN BALI - Nyoman Dane; Ida Ayu Aryani Kemenuh (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2023)
AbstractÂ Law is a rule written or unwritten, which basically applies, and is recognized by people as rules that must be obeyed in social life. The community in question consists of local people and foreign guests or tourists visiting Indonesian territory. Indonesia has a variety of islands that offer the beauty of stunning natural charm, one of which is the island of Bali. Tourism on the island of Bali can fulfill basic human needs not only for vacations and recreation, but tourism can be used to meet educational, research, religious, physical and spiritual health needs, as well as other things that are commercialized. Therefore, it is not enough for Indonesia, especially Bali, to only sell the beauty of beach, beauty of dances, beauty of panoramas, uniqueness of various culturetus because there are things that are important to protect. Protection of tourism consumers must be a common concern, both the central government, regional governments, tourism actors, and the local community. Providing protection to tourism consumers is a form of invaluable service because it offers a sense of comfort, safety and protection when tourists visit Indonesia. This legal protection should be a common concern for maintaining national stability in maintaining the continuity of tourism as a form of Indonesian tourism investment in general, and specifically for the island of Bali.Â Keywords: Legal Protection, Tourists, Tourism Investment in Bali